International barriers to parent-child communication about sexual and reproductive health topics: a qualitative systematic review. Issue 4 (4th July 2021) - Mullis, Michaela D.; Kastrinos, Amanda; Wollney, Easton; Taylor, Greenberry; Bylund, Carma L.
ABSTRACT: Research indicates that parent-child communication about sexual and reproductive health can improve safe sex practices among adolescents, but barriers to such communication exist. In this systematic review, we thematically synthesised qualitative data in 37 articles on parent-child sexual and reproductive health communication barriers conducted on five continents and in 19 different countries. We identified both barriers to communication and barriers to effective communication reported by parents and/or children. Internationally, both parents and children experienced personal barriers, such as embarrassment, discomfort and fear; communal barriers, such as outside sources and responsibility shift; and cultural barriers, such as sex as taboo, focus on abstinence and age/generational differences. Implications for future family communication interventions and measurement that could help parents navigate this form of sexual education are discussed.